Processing Cindalok Condiment Using Foam-Mat Drying Method - Alpina Evi Melianti; Maherawati Maherawati; Sholahuddin Sholahuddin; Asih Melati (FoodTech: Jurnal Teknologi Pangan, 2021)
This study was conducted to determine the effect of egg white on the physicochemical and sensory characteristics of grass jelly condiments, using a randomized block design (RAK) consisting of 1 factor 3 treatment levels, where the ratio of egg white and grass jelly concentrations was 50g: 500g, 75g: 500g, 100g: 500g used nine replications so that 27 trials were obtained. Data were analyzed statistically using the ANOVA test, followed by the BNJ test. The Friedman test analyzed organoleptic data for the best treatment using the effective index method. The best treatment of cincalok condiments was found in the ratio of egg white and cincalok concentrations of 100g:500g, namely yield of 79.78%, the water content of 7.91%, the water activity of 0.63, ash content of 4.83%, total protein of 26.03%, total acid 7.39%.